Cas9, Cpf1 and C2c1/2/3―What's next?. Issue 3 (4th May 2017) - Nakade, Shota; Yamamoto, Takashi; Sakuma, Tetsushi
ABSTRACT: Since the rapid emergence of clustered regulatory interspaced short palindromic repeats (CRISPR)-CRISPR-associated protein 9 (Cas9) system, developed as a genome engineering tool in 2012–2013, most researchers in the life science field have had a fixated interest in this fascinating technology. CRISPR-Cas9 is an RNA-guided DNA endonuclease system, which consists of Cas9 nuclease defining a few targeting base via protospacer adjacent motif complexed with easily customizable single guide RNA targeting around 20-bp genomic sequence. Although Streptococcus pyogenes Cas9 (SpCas9), one of the Cas9 proteins that applications in genome engineering were first demonstrated, still has wide usage because of its high nuclease activity and broad targeting range, there are several limitations such as large molecular weight and potential off-target effect. In this commentary, we describe various improvements and alternatives of CRISPR-Cas systems, including engineered Cas9 variants, Cas9 homologs, and novel Cas proteins other than Cas9. These variations enable flexible genome engineering with high efficiency and specificity, orthogonal genetic control at multiple gene loci, gene knockdown, or fluorescence imaging of transcripts mediated by RNA targeting, and beyond.